Producing an Educational Video - Ricky Telg; Peyton Beattie (EDIS)
The information presented in this 4-page fact sheet will assist you in developing an educational video production plan. Published by the UF/IFAS Department of Agricultural Education and Communication. Minor revision by Ricky Telg and Peyton Beattie.